Redesign and Performance Test of Liquid Fertilizer Based on Variable Rate Application on Chili Cultivation - Andi Muh. Saldan; Radi Radi; Bambang Purwantana; Lilik Sutiarso (The University of Lampung, 2024)
Liquid fertilizer applicator based on Variable Rate Application (VRA) is a technology that is used to fertilize in a controlled and precise manner. This study aims to improve the effectiveness and efficiency of the fertilization process of chili plants. The development carried out is esp32 cam which serves to detect chili plants that lack elements. The method used is input of the nutritional needs of chili plants, spray doses of each plant, and a microcontroller to control applicator components such as sprayer pumps, selenoid valve, and esp32 cam. In this liquid fertilizer applicator there are 2 pipes, each pipe has 4 nozzles. The results of laboratory tests show that the discharge of liquid fertilizer sprayed follows the input results of the nutritional needs of chili plants. The discharge released on the PWM sprayer motor varies from 40 to 100% resulting in very different discharge variations in each PWM spray. The efficiency of this VRA-based liquid fertilizer applicator reaches 87% or an increase of about 14.7% from the applicator before development. Regression analysis of dimmer level to spraying discharge showed a function y = 6.3016x + 18.937 with an R 2 of 0.9921. While the regression analysis of the dimmer level of the applicator speed obtained the function y = 94.075x + 20.203 with an R2 of 0.9936. Keywords: Chili plants, Liquid, Fertilizer, Applicator, VRA.